Family motivations and expectations in the care for psychoactive substance users - Francine Morais da Silva; Marcio Wagner Camatta; Annie Jeanninne Bisso Lachini; Cintia Nasi (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To understand the motivations and expectations of family members for the care of users of psychoactive substances. Method: This is a qualitative study using Alfred Schutz's phenomenological sociology framework. Data was collected through semi-structured interviews with family members of substance users treated in the inpatient and outpatient clinic of a university hospital in southern Brazil. Data was interpreted through comprehensive phenomenological analysis. Results: Five categories of motivation were identified: for fear and insecurity with the situation; for obligation; due to the relationship of love and connection; to stop suffering; to promote independent living. Conclusion: The motivations of the family members aim to avoid the helplessness of the substance user and to achieve positive changes in the construction of a life without the use of substances, projecting a self-sufficient future for the user.